2016
DOI: 10.1371/journal.pone.0166100
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-ARE-Dependent Alterations in Zinc Transporter mRNA Expression in HepG2 Cells

Abstract: Zinc transporters are solute carrier family members. To date, 10 zinc transporters (ZnTs) and 14 Zrt-, Irt-like proteins (ZIPs) have been identified. ZnTs control intracellular zinc levels by effluxing zinc from the cytoplasm into the extracellular fluid, intracellular vesicles, and organelles; ZIPs also contribute to control intracellular zinc levels with influxing zinc into the cytoplasm. Recently, changes in zinc transporter expression have been observed in some stress-induced diseases, such as Alzheimer’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Increasing evidence shows an effect of zinc on diabetic complications, seemingly through Nrf2. It is demonstrated that the Nrf2-ARE signal transduction pathway increases ZnT-1, ZnT-3, and ZnT-6 mRNA levels, and decreases ZnT-10 and ZIP-3 mRNA levels [ 20 ]. In this study, Nrf2 mRNA expression was found to be significantly decreased in the blood of patients with DN.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows an effect of zinc on diabetic complications, seemingly through Nrf2. It is demonstrated that the Nrf2-ARE signal transduction pathway increases ZnT-1, ZnT-3, and ZnT-6 mRNA levels, and decreases ZnT-10 and ZIP-3 mRNA levels [ 20 ]. In this study, Nrf2 mRNA expression was found to be significantly decreased in the blood of patients with DN.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously discussed zinc and citrate-mediated switching between glycolysis and TCA during PCa progression. NRF2 activation increases expression of zinc transporters (Ishida and Takechi, 2016), which efflux zinc from the intracellular organelles (such as mitochondria) and inhibits its reuptake. Therefore, higher NRF2 levels in advanced PCa help to keep zinc levels low inside the cells and in the mitochondria (Ishida and Takechi, 2016), which enhances the TCA cycle.…”
Section: Nrf2 In Metabolic Changes In Pcamentioning
confidence: 99%
“…The RNA extraction and qRT-PCR were carried out according to the procedures reported previously (Ishida and Takechi, 2016). Briefly, total RNA was extracted from HepG2 cells using the RNeasy ® Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions.…”
Section: Rna Extraction and Quantitative Real-time Polymerase Chain Rmentioning
confidence: 99%
“…The qRT-PCR assays were performed on a StepOnePlus™ real-time PCR system (Thermo Fisher Scientific) using THUNDERBIRD ® SYBR ® qPCR Mix (Toyobo) and melting curve analysis. The primer sequences and estimated product sizes have been described previously (Ishida and Takechi, 2016). The Ct value was calculated using StepOnePlus™ software.…”
Section: Rna Extraction and Quantitative Real-time Polymerase Chain Rmentioning
confidence: 99%